Consolidation of the Visco-Elastic Half-Space at Mixed Conditions of Permeability of the Boundary - Gaszyński, J.; Kumaniecka, A. (Engineering Transactions, 1977)
The exact form solution of axi-symmetric consolidation problem for a visco-elastic half-space at mixed conditions of the permeability of the boundary is presented. The process of consolidation is due to time-variable normal load acting on the boundary of the half-space. The load free boundary of the half-space is permeabile while its loaded part is not permeabile. On the basis of a coupled three-dimensional Biot’s consolidation theory with taking into account the rheological properties of the skeleton the state of stress and deformation is evaluated and the elastic skeleton the diagrams for pressure in pores under loading for different moments of time and different rates of the load increments are given.